Study on network performance evaluation method based on measurement - ZHANG Dong-yan; HU Ming-zeng; ZHANG Hong-li (Tongxin xuebao, 2006)
In order to evaluate the condition of network,a new synthetically multi-metric performance evaluation method was put forward based on multiple measurement metrics and applied to the performance evaluation of links and nets.The value of calculation reflected the performance condition of links and nets.The performance change of links and nets could be analyzed according to the different strategies using the method.The results of experiment indicate that the method can evaluate the performance of links and nets effectively.